2021
DOI: 10.1002/advs.202002228
|View full text |Cite
|
Sign up to set email alerts
|

ICAM‐1 Activates Platelets and Promotes Endothelial Permeability through VE‐Cadherin after Insufficient Radiofrequency Ablation

Abstract: Radiofrequency ablation (RFA) for hepatocellular carcinoma (HCC) often leads to aggressive local recurrence and increased metastasis, and vascular integrity and platelets are implicated in tumor metastasis. However, whether interactions between endothelial cells and platelets induce endothelial permeability in HCC after insufficient RFA remains unclear. Here, significantly increased CD62P‐positive platelets and sP‐selectin in plasma are observed in HCC patients after RFA, and tumor‐associated endothelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…45,46 (2) Activation of tumor-derived endothelial cells and platelets are implicated in cancer metastasis after insufficient thermal ablation, which could directly or indirectly cause angiogenesis and hypoxia. 11,18,19,47,48 J. Kong et al reported that insufficient RFA promoted endothelial permeability and activated platelets in tumors. 18 Besides, activation of platelets could promote the formation of neovascularization as well as thrombosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…45,46 (2) Activation of tumor-derived endothelial cells and platelets are implicated in cancer metastasis after insufficient thermal ablation, which could directly or indirectly cause angiogenesis and hypoxia. 11,18,19,47,48 J. Kong et al reported that insufficient RFA promoted endothelial permeability and activated platelets in tumors. 18 Besides, activation of platelets could promote the formation of neovascularization as well as thrombosis.…”
Section: Resultsmentioning
confidence: 99%
“…11,18,19,47,48 J. Kong et al reported that insufficient RFA promoted endothelial permeability and activated platelets in tumors. 18 Besides, activation of platelets could promote the formation of neovascularization as well as thrombosis. Z. Chen observed high expressions of VEGF and CD31 in tumors in the MW alone treated group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, genetic changes occur in the cancer cells around the ablation site when cells are subjected to thermal stimulation, and the cancer cells of incomplete ablation show more aggressive progression than untreated cells. The previous publications have proven that this experiment can imitate the biological properties similar to residual liver tumor observed clinically [22][23][24][25]. Following another 24-h culture, HepG2 xenografts were removed and immediately protected by RNAsafer Stabilizer Reagent (OMEGA, Guangzhou, China) for RNA-seq detection.…”
Section: Nude Mouse Xenograft Modelmentioning
confidence: 88%
“…RNA-seq analysis revealed downregulation of the MAPK/ERK pathway through the downstream effectors ICAM1, leading to suppress tumor growth and increase chemosensitivity of liver cancer toward chemotherapy [52]. ICAM1 inhibition could suppresses tumor growth and metastasis [53]. A prospective cohort study of 282 patients with liver disease also demonstrated the association of soluble serum ICAM1 and liver cancer development [54].…”
Section: Discussionmentioning
confidence: 99%